Broad ligament hernia successfully repaired by single‐incision laparoscopy: A case report. Issue 3 (8th November 2017) - Takeyama, Hiroshi; Kogita, Yuya; Nishigaki, Takahiko; Yamashita, Masafumi; Aikawa, Eriko; Hoshi, Minako; Taniguchi, Hirokazu; Maruyama, Yasuki; Nakajima, Kazuhiro; Yamamoto, Yoshimitsu; Adachi, Kazushige; Yamamoto, Hitoshi; et al.
Abstract: A 52‐year‐old woman with a history of two parturitions presented with lower abdominal pain. Multi‐detector CT of the abdomen showed discontinuity of the sigmoid colon near the broad ligament on the left side. We assigned a provisional diagnosis of an internal hernia progressing through a defect in the broad ligament. SILS revealed a total broad ligament defect on the left side but no signs of ischemic, necrotic bowel. We successfully repaired the broad ligament defect with suturing. At the 2‐month follow‐up, the patient remained well with no signs of recurrence. This case appears to be the first report of a broad ligament hernia successfully diagnosed and repaired by SILS.